Education Policy Polemics in Podcast Media: Unveiling Power and Ideology for Critical Literacy - Mayasari, Diana; Masae, Aleeyah; Sari, Endah (LPPI Yayasan Almahmudi bin Dahlan, 2026)
This study aims to uncover the language used in Dedi Corbuzier’s podcast through Critical Discourse Analysis (CDA). It employs a qualitative method with a phenomenological approach. The data source of this study is a podcast by Deddy Corbuzier featuring the Minister of Education, discussing polemics surrounding education policy. Data were collected through documentation, note-taking, transcription, and coding, and analyzed using data reduction, data display, hermeneutic interpretation, validity testing, and conclusion drawing. The findings reveal that, at the macro level, the discourse theme centers on controversies surrounding educational policy. At the superstructure level, the text consists of a title, lead, and storyline, while the microstructure includes syntactic and semantic elements that support the theme. Social cognition is reflected in the use of person, self, role, and event schemas by Dedi Corbuzier in interpreting Nadiem Makarim and educational policies. In social practice, power relations are evident in Nadiem’s position as minister and Dedi’s role as media owner, influencing public acceptance. CDA highlights that language is embedded with ideology and interests, making it essential for critical literacy.